HAEMORRHAGIC STROKE ON ELDERLY MAN WITH UNCONTROLLED HYPERTENSION - Norma Julianti (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2015)
Stroke is a brain disorder due to pathological processes in the blood vessels system of the brain which caused by decrease in blood flow to the brain. This process can be a blockage of the blood vessel lumen by thrombosis or embolism, rupture of the blood vessel of the brain that causes bleeding, changes in the permeability of the blood vessel walls and changes in blood viscosity and quality. This case report taken from Abdul Moeloek hospital in July 2014. A man, 54 years old, came with a sudden loss of consciousness. One day before hospital admission, the patient still able to do his activity then patient suddenly had difficulty in walking. A fewdays before, patient suffered from headache and vomiting. One month before, the patient had a weakness at the right arm and leg. Physical examination found blood pressure was 200/100 mmHg, neurological status found pathological reflex, babinski and chaddock reflex. Patients was diagnosed with haemorrhagic stroke. Patient was treated with mannitol infusion, ranitidine injection 50 mg every 8 hours, ceftriaxone injection 1g every 12 hours, citicolin injection 250 mg every 12 hours, captopril tablet 25 mg every 8 hours, B complex tablet 100 mg every 12 hours. Haemorrhagic stroke in these patients is caused by uncontrolled hypertension. [J Agromed Unila 2015; 2(1):32-38]Keywords: haemorrhagic stroke, man, neurologic, uncontrolled hypertension